Magneli-Phases in Anatase Strongly Promote Cocatalyst-Free Photocatalytic Hydrogen Evolution - Domaschke, Maximilian; Zhou, Xuemei; Wergen, Lukas; Romeis, Stefan; Miehlich, Matthias; Meyer, Karsten; Peukert, Wolfgang; Schmuki, Patrik (ACS Catalysis, 2019)
Magneli phases of titanium dioxide (such as Ti4O7, Ti5O9, etc.) provide electronic properties, namely, a stable metallic behavior at room temperature. In this manuscript, we demonstrate that nanoscopic Magneli phases, formed intrinsically in anatase during a thermal aerosol synthesis, can enable significant photocatalytic H-2 generation-this without the use of any extrinsic cocatalyst in anatase. Under optimized conditions, mixed-phase particles of 30% anatase, 25% Ti4O7, and 20% Ti5O9 are obtained that can provide, under solar light, direct photocatalytic H-2 evolution at a rate of 145 mu mol h(-1) g(-1). These anatase particles contain 5-10 nm size intergrown phases of Ti4O7 and Ti5O9. Key is the metallic band of Ti4O7 that induces a particle internal charge separation and transfer cascade with suitable energetics and favorable dimensions that are highly effective for H-2 generation.
CRIS-Team WoS Importer:2019-04-23